2015
DOI: 10.1016/j.ejcdt.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of serum uric acid in acute respiratory distress syndrome patients: A preliminary study

Abstract: Background: ARDS mortality is still high, many biomarkers had been used to predict the mortality but they may have many drawbacks because of its validity, complications and cost.Study design: Observational study was planned to evaluate the predictive role of serum uric acid level in ARDS outcome. Mortality was the primary end-point while secondary endpoints included total ICU stay, duration of mechanical ventilation and the presence or absence of complications.Aim: The aim of this work is to study the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, a recent study suggested that hyperuricemia may be associated with increased mortality in patients with ARDS. 25 In patients with COPD, a high uric acid level correlated significantly with the severity of disease or degree of hypoxemia and future exacerbation or mortality. 12,26 Another study reported that serum uric acid level increased with the severity of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 97%
“…However, a recent study suggested that hyperuricemia may be associated with increased mortality in patients with ARDS. 25 In patients with COPD, a high uric acid level correlated significantly with the severity of disease or degree of hypoxemia and future exacerbation or mortality. 12,26 Another study reported that serum uric acid level increased with the severity of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 97%
“…Among various biochemical parameters, serum LDH and Serum UA have been associated with the severity of COVID-19 disease. In one study, LDH was elevated in 41% of COVID-19 patients 2 while in a pooled analysis of 9 published studies (n=1532 COVID-19 patients), elevated LDH levels were associated with a ~6-fold and ~16-fold increase in odds of developing severe disease and mortality in COVID -19 patients, respectively 3 Similarly, another study reported that Serum UA level at 8.4 mg/dl cut off point had 89% sensitivity and 80% specificity predicting higher mortality, more severe ARDS, and frequent occurrence of multiple organ dysfunction syndromes 10 . On the other hand, In one study, increased LDH and UA were seen in 96.6% and 83.3% leukemic patients, respectively 7 .…”
Section: Discussionmentioning
confidence: 98%
“…Statistical analyses were performed as described in Elshafey et al [17] Briefly, SPSS was applied for statistical testing significance. Quantitative data were analyzed by mean ± SD using the 2-tailed student unpaired t test while the chi-squared test was used to assess the significance of qualitative data.…”
Section: Methodsmentioning
confidence: 99%